2021
DOI: 10.3384/ecp182p26
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sliding Mode Controller for Classical and Direct Driven Electrohydraulic System

Abstract: In this paper, a novel energy-efficient Direct Driven Hydraulic (DDH) drive is made in parallel with a classical valve-controlled proportional electrohydraulic system. In the proposed concept asymmetrical hydraulic cylinder is controlled with two reversible pumps directly connected to a servo motor. Due to direct control of the oil flow, such system provides higher energy efficiency in comparison to a valve-controlled hydraulic system. The experimental setup is designed with the possibility of easy switching b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In the case when the cylinder is pulled in, additional input power emerges from the potential energy of the load. Consequently, the input system energy is defined as the sum of integrals of all input powers and the output system energy as an integral of output power from [22] as:…”
Section: Experimental Investigation Into Energy Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…In the case when the cylinder is pulled in, additional input power emerges from the potential energy of the load. Consequently, the input system energy is defined as the sum of integrals of all input powers and the output system energy as an integral of output power from [22] as:…”
Section: Experimental Investigation Into Energy Efficiencymentioning
confidence: 99%
“…It has been shown that for temperatures below zero, high-performance oil has almost 10% higher efficiency than the conventional multi-grade oil. Different control methods for a DDH system are compared in [22] where PID controller achieved the highest energy efficiency while the sliding mode controller obtained faster dynamics with a slightly lower energy efficiency. The preliminary results presented in [23] showed that the DDH system could also greatly increase the overall efficiency of the skidder powertrain.…”
Section: Introductionmentioning
confidence: 99%